The hidden threats posed by Japanese encephalitis virus genotype V - Li, Qi; Mishra, Hridesh; Kain, Kevin C.; Wang, Ran (Journal of virology, 2025)
Japanese encephalitis virus (JEV) remains a major cause of viral encephalitis in Asia. Among its five genotypes (GI-GV), genotype V (GV) has re-emerged and become the predominant lineage in mosquitoes in the Republic of Korea, with sporadic human cases also reported. GV JEV displays differences from other genotypes in genomic sequence, antigenicity, and pathogenicity, and animal studies indicate higher lethality. Importantly, all currently used vaccines are based on GIII strains and provide partial but insufficient protection against GV JEV, with breakthrough infections documented. These findings raise concerns that GV circulation could undermine existing control strategies. Although shifts in mosquito vectors have been observed, the broader epidemiological and clinical impact of GV JEV remains poorly defined. In the absence of specific antiviral therapies, systematic evaluation is needed to determine whether GV-based vaccines are warranted. This review summarizes current evidence on the epidemiology, molecular and biological characteristics, and vaccine protection of GV JEV, and highlights priorities for surveillance and future research.